Dermoscopic Evaluation of Longitudinal Melanonychia in Children: A Prospective Study - Mahshid Sadat Ansari; Hamidreza Mahmoudi; Ali Sadeghinia; Shadi Azizzadeh-Roodpishi; Alireza Ghanadan; Maryam Daneshpazhooh (Wolters Kluwer Medknow Publications, 2021)
Background: Longitudinal melanonychia (LM) is a worrisome sign in both children and adults. Nail apparatus melanoma (NAM) can be related to LM, but it is very rare in children. Dermoscopic signs of benign lesions in children can be similar to melanoma; therefore, it is important to review dermoscopy of LM in children to make the best decision in performing biopsy. Aims: Biopsy taking is very challenging in LM in children. Most lesions are benign in children. The aim of this study was to review dermoscopic signs of LM in children and compare them with adults. Materials and Methods: In this prospective study a total of 108 LM (35 children and 73 adults) were undergone dermoscopy of LM. Dermoscopic features were compared in children and adults; both for benign lesions proven by biopsy or follow up and melanomas diagnosed histopathologically. Results: Black background, black band color, band color diversity and pseudo-Hutchinson's sign were more frequent in children in comparison with benign adult melanonychia. Some children's dermoscopic features of LM such as broad band width, Band color diversity, Hutchinson's sign, gray band color, asymmetry of pattern, and regression were similar to melanoma, but we did not find any melanoma by biopsy and/or follow up among children. We also detected the newly described "zigzag" pattern in four children. Conclusion: Dermatologists should consider all dermoscopic features of a lesion, dermoscopic sign changes in follow-up, medical, and familial history of the patient in deciding to perform biopsy of LM in children.